Analisis Marketing Influencer dan Emotional Buying Produk Skincare Merek Somethinc - Filah Pebrianti,; Rahila Anggani,; Trie Ayu Lestari,; Helin Garlinia Yudawisastra, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Something about  influencer marketing analysis on emotional buying behavior for Somethinc skincare products. Using a literature study method, the research found that the credibility and authenticity of influencers such as Tasya Farasya serve as effective psychological instruments in reducing risk perception and triggering consumer emotional engagement. The analysis results show that this strategy is able to increase purchase intent by up to 30% through persuasive and honest content. Among Generation Z, emotional buying is driven by the need for social validation and instant gratification triggered by visual social proof on social media. In conclusion, Somethinc's success lies in the ability of influencers to integrate the value of “self-care” with credible digital marketing strategies.